The Effect of Ethylmethylhydroxypyridine Succinate on the Dynamics of Cerebral Blood Flow Patterns in Patients with Acute Concomitant Traumatic Brain Injury - E. A. Abramova; O. V. Voennov; G. A. Boyarinov; A. O. Trofimov (Общая реаниматология, 2017)
The purpose of the investigation was to study the effect of the ethylmethylhydroxypyridine succinate (EMHPS) infusion on the dynamics of cerebral blood flow patterns in patients during the acute phase of severe concomitant traumatic brain injury. Materials and methods. The study involved two groups of patients, each of 25 persons aged 41.5 (29; 51) years on average, with a severe concomitant traumatic brain injury. The patients of the 1st (control) group were cured with a standard intensive care while in the 2nd (study) group the EMHPS infusion was added to the said standard treatment in a dose of 100 mg per hour through an infusion pump within 10 days. By transcranial dopplerography (TDG) testing the following cerebral macrocirculation parameters (CMP) were studied: systolic blood flow velocity (Vmax), diastolic blood flow velocity (Vmin), pulsation index (PI) and resistance index (RI). Results. The most frequent type of the cerebral blood flow (CBF) disorder noted in the both groups during the initial examination was a hindered perfusion pattern noticed in 15 and 16 patients from 1st and 2nd groups, respectively. Mild vasospasm was recorded in four patients in the 1st group and in three cases in the 2nd group. Signs of gross vasospasm were noted in two patients from each group. In two patients of each group patterns of hypoperfusion and hyperperfusion were noted. In the patients of the 1st group the CMP normalization was observed in six cases on the third day, in eight cases on the fifth day, in 12 cases on the seventh day, in 18 cases on the 10th day, while in the patients of the 2nd group the CMP normalization was observed on the 3rd day in 12 cases, on the 5th day in 15 cases, on the 7th day in 16 cases and on the 10th day in 20 cases. Conclusion. The most common patterns identified during the initial examination included hindered perfusion and vasospasm, which were transformed into a normoperfusion pattern through the hyperperfusion stage (reactive hyperemia). The EMHPS infusion in a dose of 100 mg per hour usually aids to normalize parameters within 3—5 days.